The Effects of Different Total Acid Content in Malt on the Physicochemical Properties and Flavor of Beer - LI Xiao-yan; ZHAO Kai; DU Yi-jun; CHEN Wen-bo; LI Hui; YU Zhong-zhao (Liang you shipin ke-ji, 2024)
Different malt samples with various total acid content were used to brew beer. The organic acid content in both the malt and the brewed beer was measured by using high-Performance liquid chromatography (HPLC) to establish the correlation between the total acid content in malt and the organic acid content in the beer. Additionally, gas chromatography-mass spectrometry (GC-MS) was used to detect the components of volatile compounds in the beer, and sensory evaluation was employed to assess the brewed beer's qualities. The results indicated that as the total acid content in malt increased, the pH value gradually decreased, and the content of succinic acid, malic acid, lactic acid, and acetic acid increased. There was a significant positive correlation between the total acid content in malt and the total acid content, malic acid content, and lactic acid content in the beer, with correlation coefficients of 0.94, 0.94, and 0.92, respectively. Different malt samples with varying total acid content demonstrated different characteristic aroma compounds in the brewed beer, contributing to differences in sensory attributes. As the total acid content in malt increased, the perceived acidity score of the brewed beer increased, while the scores for hop/fruit aroma, phenolic aroma, and alcohol perception decreased.